KEKERASAN SUAMI TERHADAP ISTRI DALAM WACANA HAK ASASI MANUSIA - Zuhriah, Erfaniah (EGALITA, 2007)
All sort of physical and phsycological violences generating from gender bias practices toward role and position of women in the family are legally not allowed based on international declaration on Human rights as those violences neglect basic rights of individuals. Domestic violence, as one example of gender bias practice, is legally prohibited for its subordination, marginalization and streotype toward men or women in a domestic relationship context. It maybe safely argued that any forms of differences which are constructed based on gender bias perspective may result in inequality and violences. Therefore, gender role division refers to husband-wife right and obligation under religious normative doctrines and socio-cultural understanding are not tolerated and can be categorized as breaking the legal regulation of human rights.